Characterizing Energy Usage of a Commercially Available Ground Robot: Method and Results. Issue 3 (21st March 2014) - Broderick, John A.; Tilbury, Dawn M.; Atkins, Ella M.
<x xml:space="preserve">Abstract</x> Energy usage by mobile robots is becoming a larger concern as autonomous systems increase mission durations. Understanding and characterizing energy usage is key to reliable mission operation. This paper presents a methodology for characterizing energy usage of a ground robot traveling at a constant speed applicable to both open and "black box" (proprietary) platforms. To address testing area limitations, we introduce a "rounded box" path to approximate straight line travel. For a case study, this methodology was applied to an iRobot Packbot on grass and asphalt surfaces. Our results show a decrease in electrical energy used with increasing speed for soft grass and constant energy usage on asphalt. For both surfaces, a similar electrical‐to‐mechanical efficiency curve is obtained.